Production of jets at forward rapidities in hadronic collisions - Hautmann, F (2010)
We discuss high-pT production processes at forward rapidities in hadron-hadron collisions, and describe recent results on using QCD high-energy factorization in forward jet production at the LHC. © Società Italiana di Fisica / INFN - Laboratori Nazionali di Frascati.